Aeroengine - TAYLOR MARK DAVID; HOWARTH NICHOLAS; PARRY ANTHONY BRIAN (2013)
A method of operating a contra-rotating propeller engine that preferably comprises a 12 bladed front and a 9 bladed rear propeller. As is conventional, the engine is operated during at least a take-off phase, a cruise phase and an approach phase; during the cruise phase the engine operates with a generally constant propeller tip speed. The method is characterized by the step of operating the engine such that the tip speed of either or both of the propellers, during at least one of take-off, climb or approach, at least 10% greater than cruise tip speed. With a specific front to rear propeller spacing, increasing the tip speed reduces overall noise generated by the propellers.